Cambial dormancy lasts 9Â months in a tropical evergreen species - de Lara, Natália Oliveira Totti [UNESP]; Marcati, Carmen Regina [UNESP] (Springer Nature, 2016)
Key message: Cambial dormancy in a tropical evergreen species is long lasting, and the initiation of cambial activity is related to day length. Abstract: Studies on cambial activity allow us to understand the growth dynamics of plants. In this study, we investigate cambial activity and the conducting phloem in a population of an evergreen shrubby species from a semi-deciduous tropical forest with distinct wet and dry seasons. Stem samples from Cordiera concolor were collected bimonthly in 2010 and prepared according to the standard methods for plant anatomy. The relationship between cambial activity and climate factors as well as phenology was investigated using Spearman’s correlation. The cambium is dormant during the rainy season and dormancy lasted up to 9Â months. Cambial activity was positively related to day length, and although it occurred in the rainy season, the period of its onset and termination was not concurrent with the beginning and end of the rainy season. The conducting phloem corresponded most to the non-collapsed phloem and was present year-round, ranging in width (in transverse section) from 62Â Âµm in the rainy season to 112Â Âµm in the dry season. Together, these results illustrate that cambial activity in an evergreen species of a seasonal tropical forest is seasonal with long-lasting cambial dormancy, and that at least some conducting phloem is present year-round.
Keywords: Cambial activity; Cambial dormancy; Cordiera concolor; Evergreen species; Secondary phloem; Tropical species